2003
DOI: 10.1002/cncr.11650
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cyclooxygenase‐2 expression on tumor vascularity in advanced stage ovarian serous carcinoma

Abstract: In der Domäne gefangen: Die Fähigkeit von polaren und unpolaren Domänen in ionischen Flüssigkeiten, Reaktionen durch Pseudoverkapselung von Reaktanten zu beeinflussen, wurde in nukleophilen Substitutionen mit einem kationischen Substrat und einer Reihe von Nukleophilen untersucht. Eine signifikante Reaktionsbeschleunigung wurde beobachtet, die mit der Konzentration der polaren Reagentien innerhalb der polaren Domänen der ionischen Flüssigkeiten korreliert ([CnMIM]=1‐Alkyl‐3‐methylimidazolium).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 21 publications
4
52
1
Order By: Relevance
“…10 One study investigated the expression of both COX-1 and COX-2 isozymes in normal and malignant ovarian epithelium. 25 COX-1 and COX-2 proteins were present in 69.3% and 70.8%, respectively, of all tumors studied. Notably, COX-2-positive staining seemed significantly higher in the metastatic than in the primary sites.…”
Section: Recently Kurman Et Al Proposed a New Classification Ofmentioning
confidence: 92%
See 2 more Smart Citations
“…10 One study investigated the expression of both COX-1 and COX-2 isozymes in normal and malignant ovarian epithelium. 25 COX-1 and COX-2 proteins were present in 69.3% and 70.8%, respectively, of all tumors studied. Notably, COX-2-positive staining seemed significantly higher in the metastatic than in the primary sites.…”
Section: Recently Kurman Et Al Proposed a New Classification Ofmentioning
confidence: 92%
“…Several recent studies have shown that COX-2 is overexpressed in epithelial ovarian and primary peritoneal cancers and that overexpression correlates with worse clinical behavior. [25][26][27][28][29] COX-2 overexpression was noted in 65% to 75% of serous ovarian carcinomas studied. It was associated with increased tumor vascularity.…”
Section: Recently Kurman Et Al Proposed a New Classification Ofmentioning
confidence: 93%
See 1 more Smart Citation
“…Low expression was defined as intensity 0, 1, 2 or 3 and o10% cells staining or intensity 0, 1 and o50% cells staining; high expression was defined as intensity 2, 3 and 410% cells staining or intensity 1, 2, 3 and 450% of cells staining. 18 To determine Ki-67 and p53 expression, nuclei from at least 1000 tumor cells were counted from the tumor fields, and the labeling index was calculated as the percentage of labeled nuclei of the total number of tumor cells that were counted. 19 Tumors with a Ki-67 labeling index above 44% (median value) were considered to have high proliferation indices.…”
Section: Assessment Of Antibody Expressionsmentioning
confidence: 99%
“…Aoki et al 54 reported gene expression of cox-2 to be correlated with that of bcl-2 in pleomorphic adenoma and Tatsaguchi et al 55 found both bcl-2 expression and low apoptosis to be closely related to cox-2 expression in gastric cancer cells, and moreover, cox-2 and bcl-2 protein levels to be correlated with each other. On the other hand, Sweeney et al 56 did not observe any correlation between cox-2 and bcl-2 protein in lung or bladder cancer specimens and Ali-Fehmi et al 57 observed no association between cox-2 and bcl-2 levels in ovarian carcinoma. Again, it is difficult to tell whether these discrepancies really indicate differences in the mechanism of cox-2 activity among tumor types or result from technical problems associated with the use of semiquantitative IHC methodology, which can have standardization issues related to using different antibodies, staining and scoring protocols.…”
Section: Discussionmentioning
confidence: 95%